Characters of Nutrition Status and Energy-delivery Patterns of the University-based Surgical Intensive Care Units in Thailand (Multi-center THAI-SICU Study) - Supakrit Auiwattanakul (2018)
Aim: The authors aimed to describe nutrition status and energy-delivery characters in multi-center THAI-SICU study.Material and Methods: Eligible patients admitted in SICU were 1,686 after excluding 563 of 2,249 participants owing to very short stay or non-alive within 24 hours after admission and missing data. The study was a posthoc analysis and multicenter descriptive design. The analytic methods described categorical data in percentage and the continuous data in the median with interquartile range. Variables divided into baseline characteristics and nutrition data before SICU admission, and the pattern of energy delivery in SICU. Statistical significance accepted as a p-value less than 0.05.Results: The average age was 64 (52-76) years with 57% male. The median of serum albumin level at admission (interquartile range, IQR) was 2.8 (2.2-3.4). There was 46 -47 percent of nutrition risk patient. Less than 10 percent of the patient had enteral (EN), parenteral (PN) or their combination before admission. History of weight loss and appetite loss was 27-31 percent. However, seventy percent of the patient could not define the duration of the symptom. EN was initiated early, but the tendency of full feeding was 7-10 days. At that period, supplemental PN was added around 30 percent of total calories. The composition of PN was quite low in these study which contains only 15-16 percent of total calories. The average energy delivery was 20 kcal/kg/day (the recommendation is 25-30 kcal/kg/day).Conclusion: The patient's nutrition status before SICU admission was at risk of 46-47% and weight loss and appetite loss might unreliable in ICU setting. EN is started early with gradually increase up to 7-10 days. The average total calories requirement is lower than a recommendation.